Impact of Campaign Regulations on Electoral Freedom: Dampak Peraturan Kampanye terhadap Kebebasan Memilih - Hamjad, Hamjad; Asmara, M. Galang; Cahyowati, Roro (Indonesian Journal of Law and Economics Review, 2024)
This research scrutinizes Constitutional Court Decision No. 65/PUU-XXI/2023, focusing on the intersection of campaign regulations and the fundamental right to electoral choice in a democratic society. Using a normative legal research methodology, the study delves into the legal concepts, principles, and norms governing electoral campaigns, particularly regarding their conduct in educational institutions and government facilities. This approach is both descriptive and normative, relying on existing legislation, court decisions, and supplementary academic sources to construct a comprehensive understanding of the subject. The research identifies a lack of clarity in current regulations about campaigning in educational spaces, as highlighted by the absence of specific legal guidelines in this area. The analysis of the Constitutional Court's decision and related electoral laws, including Article 280 of the 2017 General Election Law, reveals a need for more precise legal provisions to regulate campaign mechanisms and concepts effectively. The findings suggest that while existing laws aim to uphold citizens' political rights to free choice, they lack detailed implementation strategies, particularly concerning youth engagement in political processes. The study advocates for policymakers and government officials to develop legal frameworks that extend campaign outreach not only to the non-educational population but also to young voters, fostering their involvement and understanding of political contests. This would contribute to the national goal of informed and active citizenship.Highlights: Ambiguity in Campaign Regulations: The study highlights the lack of clear guidelines for conducting electoral campaigns in educational settings. Constitutional Court's Influence: Examines the impact of Decision No. 65/PUU-XXI/2023 on the balance between free political choice and regulated campaigning. Youth Political Involvement: Emphasizes the need for legal reforms to enhance the political engagement and education of young voters. Keywords: Electoral Campaign Regulation, Constitutional Court Decision, Political Rights, Youth Engagement, Legal Framework